Considering the Nature of Science Content Knowledge and Pedagogical Content Knowledge in Canadian Science Education Programs: An Environmental Scan - Watson, Ellen; Ragoub, Sarah (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2025)
Science education scholars agree that it is important for teachers to be prepared to teach science as more than facts and information. Part of this preparation is understanding the nature, history, and philosophy of science and its impact on scientific knowledge. However, research has shown that science teachers are often unfamiliar with the ideas underpinning their discipline. To investigate teachers’ preparation, this study presents the results of an environmental scan of secondary science-education programs across Canada, with respect to the inclusion of the nature, history, and philosophy of science in their course descriptions. Using pedagogical content knowledge as a framework, the exposure of future Canadian secondary-science teachers to the nature, history, and philosophy of science in their content and pedagogical content courses is described. The implications of the lack of inclusion of the nature, history, and philosophy of science in the course descriptions of secondary science teacher education programs are discussed.